Breeding biology of two wagtail subspecies on Ulleung Island, Korea: Amur Wagtails, Motacilla alba leucopsis and Black-backed Wagtails, M. a. lugens. Issue 4 (4th July 2018) - Lee, Ji-Young; Park, Jin-Young; Kim, Incheol; Kim, Woo-Yuel; Sung, Ha-Cheol
ABSTRACT: There is much controversy over the species and subspecies status of the white wagtail complex, which is further compounded by interbreeding between two subspecies, the Amur Wagtail ( Motacilla alba leucopsis ) and the Black-backed Wagtail ( M. a. lugens ). This study presents preliminary information on the breeding biology of both subspecies on Ulleung Island, Korea, over two breeding seasons (2012–2013). Mixed pairs of the two subspecies were common on this island, with almost 50% of all pairs being heterotypic or intermediate pairs; however, assortative mating was still present. Females of both subspecies were more likely to be paired with Amur wagtail males, whereas intermediate females were more likely to be paired with Black-backed Wagtail males. Clutch size, egg size and mass, and reproductive parameters (such as hatching success and nest success) did not significantly differ from each other. However, the mean values were low in intermediate pairs. Our results indicate no reproductive barrier between the two subspecies, but that some post-isolating mechanisms are still in progress.